Freedom of expression and combating disinformation: The STF and the Principle of Proportionality in post-expression accountability - Morais, André Veloso Machado Guerra de (2025)
This study addresses the challenge of balancing freedom of expression with combating disinformation within the Brazilian legal context, focusing on the application of the principle of proportionality by the Federal Supreme Court (STF). Freedom of expression, recognized as a fundamental right and a pillar of democracy, faces limitations when it conflicts with values such as human dignity and the protection of public order. In this scenario, the STF plays a central role in interpreting conflicts between the right to freedom of expression and the need for accountability for abusive manifestations, especially in cases involving the proliferation of disinformation and hate speech. The general objective of this study is to analyze how the STF has balanced these fundamental rights. The research adopts a qualitative, exploratory, and theoretical approach, based on the hypothetical-deductive method. It relies on a bibliographic review of authors such as Schauer (1982) and Dworkin (1996), as well as jurisprudential analysis of landmark cases such as ADPF 130, RE 1010606, and Inquiry 4781. The results reveal that the STF takes a dynamic stance, using the principle of proportionality to weigh conflicting values. Decisions such as the declaration of unconstitutionality of the Press Law in ADPF 130 reinforce the prohibition of prior censorship, while post-expression accountability, as in RE 1010606, highlights the protection of historical memory and collective interests. In Inquiry 4781, the STF demonstrates judicial activism in addressing digital disinformation, holding actors and platforms accountable for illicit practices. The study concludes that the STF has sought to consolidate a balance between freedom of expression and combating disinformation, aligning itself with contemporary theories of law and political philosophy. However, its activist stance in certain cases raises debates about the limits of its role and the impacts on legal certainty and digital governance in Brazil.